Program on Violence against Women and Children for DKI Jakarta residents - Dewi Prabawati; Lina Anggraeni; Regina Novita; Ni Nyoman Artina (Universitas Serang Raya, 2022)
The pandemic of Covid-19 bring poor influence in various aspects such as the economy, health and finance. Increased problems and stress have an impact on domestic violence against women and children. It was reported the incidence of domestic violence increased during the pandemic as a result of stresses and uncertainty condition, especially when there is an imbalance of authority between men and women at home. There were 80% of female respondents in the middle to lower economic level reported receiving psychological and economic violence, and the implementation of Community Activity Restrictions (PPKM) in DKI Jakarta forced victims to live in the same house as the perpetrators of violence. For this reason, a program for an anti-violence campaign against women and children is needed with the aim to increase the awareness of women/wives due to domestic violence impact both for themselves, children and families. This program is carried out by academics through some events such as webinars, sharing messages through social media and launching the SAPA Pos (Friends of Women and Children) as a service forum for residents who need services and support. With a good understanding of violence, it is expected that DKI Jakarta residents will be more concerned in preventing violence experienced by women and children and have the courage to speak up/report it.